DAMPAK KEBERADAAN PENYAKIT PADA PROSES PENYIMPANAN TERHADAP PENDAPATAN PEDAGANG CABAI MERAH BESAR DI KABUPATEN ALOR - Didiana Y. Molebila; B. Djou B. Padafani; Zoimath N. R. Achmad (Politeknik Pertanian Negeri Kupang, 2023)
Anthracnose and bacterial wet rot are types of red chili diseases that are often found during the storage process. This research aims to determine the impact of storage disease in large red chilies on the income of traders in Alor Regency. The sample consisted of 20 trader respondents to obtain data on traders' income, and 1/2 kg of large red chilies per trader, then taken to the laboratory to observe and calculate the incidence, as well as the severity of the storage disease. Data was obtained through direct observation and interviews. Data analysis used simple regression analysis with the SPSS version 22 application. The results of the research found two types of disease in large red chili fruit storage, namely anthracnose and wet rot bacteria which were classified in the high and susceptible disease category with an average disease incidence of 15.54%-39 .84% and disease severity reached 66.36%-95.17%. Regression analysis shows that wet rot bacteria have a negative and significant effect on traders' income, where if there is an increase in disease severity of 1%, traders' income will decrease by 2.55% or Rp. 198,121.61.Keywords: Anthracnose, Bacterial Wet Rot, Chili Traders, Income